Scorpion. Season one [videorecording (DVD)] - Gabel, Elyes, 1983-; McPhee, Katharine, 1984-; Patrick, Robert, 1958-; Thomas, Eddie Kaye, 1980- (Paramount Home Entertainment, 2015)
When Scorpion is on the case, saving the world is a no-brainer! Walter, the eccentric leader of a team of brilliant misfits -- a psychiatrist with a gambling addition, a mechanical prodigy with anger issues, and a "human calculator" with social anxiety, who save the world from problems only a genius could solve.